2010
DOI: 10.1007/s12034-010-0074-0
|View full text |Cite
|
Sign up to set email alerts
|

Erosive wear of a surface coated hydroturbine steel

Abstract: In the present investigation, stellite-6, Cr 3 C 2 -NiCr and WC-Co-Cr coatings were deposited by DGun on a hot rolled 21Cr-4Ni-N steel meant for fabrication of hydro turbine underwater parts. The coatings have been characterized for microstructure, porosity, microhardness and crystalline nature. The erosion experiments were carried out using an air jet erosion test rig at a velocity of 120 ms -1 and impingement angles of 30° and 90°. Silicon carbide particles of size ranging between 500 and 700 µm were used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
(21 reference statements)
1
8
0
Order By: Relevance
“…7 Detonation coatings are designed for applying hard materials, especially carbides, on surfaces subject to aggressive wear. [8][9][10] Cr 3 C 2 -NiCr system coatings have major applications in components that are used in high temperature wear resistance and corrosion resistant industries like aerospace and powder engineering.…”
Section: Stages Of Corrosionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Detonation coatings are designed for applying hard materials, especially carbides, on surfaces subject to aggressive wear. [8][9][10] Cr 3 C 2 -NiCr system coatings have major applications in components that are used in high temperature wear resistance and corrosion resistant industries like aerospace and powder engineering.…”
Section: Stages Of Corrosionmentioning
confidence: 99%
“…7 Detonation coatings are designed for applying hard materials, especially carbides, on surfaces subject to aggressive wear. 810…”
Section: Introductionmentioning
confidence: 99%
“…It has been documented that thermally sprayed coatings with thickness 200-400 mm can effectively protect the components with economic viability (Chauhan et al, 2010). Therefore, for the water with high particles sizes, nickelbased tungsten carbide coating is preferred to increase the ductility of the turbine components.…”
Section: Hydroturbinesmentioning
confidence: 99%
“…Hussainova et al (2007) investigated the effect of Ni content on the wear behaviour of Cr 3 C 2 -based cermets and found that the wear rate decreases with an increase in hardness due to decreasing Ni content. Chauhan et al (2010) evaluated the high impact angle erosion wear characteristics of Cr 3 C 2 -NiCr and WC-Co cermets coatings, comparatively. 75Cr 3 C 2 -25NiCr coatings showed higher wear resistance than WC-Co coatings at 90 • due to good binder wettability and high ductility of the binder phase which prevent further material removal (Chauhan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Chauhan et al (2010) evaluated the high impact angle erosion wear characteristics of Cr 3 C 2 -NiCr and WC-Co cermets coatings, comparatively. 75Cr 3 C 2 -25NiCr coatings showed higher wear resistance than WC-Co coatings at 90 • due to good binder wettability and high ductility of the binder phase which prevent further material removal (Chauhan et al 2010). Huang et al investigated the mechanical properties of VC, Cr 3 C 2 and NbC doped WC-Co cermets and found that pure WC-Co cermet had a lower hardness than that of doped cermet.…”
Section: Introductionmentioning
confidence: 99%